2019
DOI: 10.1101/635078
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

AML ImmunoPET:64Cu-DOTA-anti-CD33 PET-CT imaging of AML in Xenograft mouse model

Abstract: provides consulting for Amgen and Stemline and is on the speakers' bureau for the former company. Joseph Rosenthal receives honoraria from and consults for Shire and Bayer, and receives research funding from Daiichi Sankyo and Kite Pharma. All other authors declare no competing financial interests. Abstract: 245 words Translational relevance: 153 words Abstract: Purpose:Acute myeloid leukemia (AML) is a highly aggressive form of leukemia that results in poor survival outcomes. Currently, diagnosis and prognosi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(7 citation statements)
references
References 35 publications
0
7
0
Order By: Relevance
“…The findings support the potential use of this imaging modality for noninvasive detection of AML in humans and monitoring treatment response [139]. Subsequent research by Allen et al focused on [ 89 Zr]Zr-labeled lintuzumab molecule, showing promising results in PET imaging of CD33 positive human AML tumors [140].…”
Section: Immunopetmentioning
confidence: 57%
See 3 more Smart Citations
“…The findings support the potential use of this imaging modality for noninvasive detection of AML in humans and monitoring treatment response [139]. Subsequent research by Allen et al focused on [ 89 Zr]Zr-labeled lintuzumab molecule, showing promising results in PET imaging of CD33 positive human AML tumors [140].…”
Section: Immunopetmentioning
confidence: 57%
“…The results showed high sensitivity and specificity, highlighting spatial heterogeneity in the disease based on disease burden [139]. This suggests caution in interpreting results from single bone marrow biopsies [139].…”
Section: Immunopetmentioning
confidence: 98%
See 2 more Smart Citations
“…Currently, two PET enabling radionuclides are routinely available to the nuclear medicine community: Gallium-68 ( 68 Ga), a trivalent positron radiometal with a short physical half-life of 68 min and Zirconium-89 ( 89 Zr), tetravalent radiometal with a half-life of 78.4 h. 68 Ga half-life does not match the several days long biological half-life of full-size antibodies; 89 Zr half-life provides a better match. Recently pre-clinical imaging of acute myeloid leukemia (AML) models with Copper-64 ( 64 Cu) has been reported [ 4 ], however, both short-physical half-life of 64 Cu (12.7 h) and its not being readily available limit its use as a research tool for biodistribution and pharmacokinetics of antibodies. It has been demonstrated that targeting CD33 with lintuzumab antibody radiolabeled with 225 Ac has promising activity in patients with relapsed/refractory AML in phase 1/2 clinical trials [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%